Pengaruh Kombinasi Ekstrak Etanol Daun Beluntas (Pluchea indica Less.) dan Daun Sukun (Artocarpus altilis (Park.) Fosberg) terhadap Bakteri Staphylococcus aureus ATCC 25923 - Setyowati, Rini; Indrayati, Ana; Sari, Ghani Nurfiana Fadma (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Indonesians are frequently afflicted with infectious diseases caused by the Staphylococcus aureus bacteria. Beluntas and breadfruit leaves contain flavonoids, saponins, alkaloids, and tannins which have potential as antibacterials. This research seeks to the impact of mixing ethanol extracts of breadfruit and beluntas leaves on S. aureus ATCC 25923. Powder were macerated using 96% ethanol followed by identification of the compound class. Single extracts were examined for dilution to acquire effective concentrations before being mixed with concentration ratios of 1:1, 1:2, and 2:1. The extracts combination was tested using the disc diffusion method, and the combination effect was tested using the paper tape method. The results demonstrated that the beluntas and breadfruit leaf extracts had MBC value of 12.5% and 6.25%. The most effective extract combination was at a concentration ratio of 2:1, with an average diameter of the inhibition zone of 20.72 mm, while the ratios of 1:1 and 1:2 were only 17.78 and 18.15 mm, respectively. The combination effect of extracts is synergistic